2008
DOI: 10.1167/iovs.07-1234
|View full text |Cite
|
Sign up to set email alerts
|

Nrl-Knockout Mice Deficient in Rpe65 Fail to Synthesize 11-cisRetinal and Cone Outer Segments

Abstract: The findings provide clarification of reported cone loss of function in Rpe65(-)(/-)/Nrl(-)(/-) mice, now showing that chromophore absence results in destabilized cone outer segments and rapid retinal degeneration. The data support the view that rod-dominant retinas do not have a cone-specific mechanism for 11-cis retinal synthesis and have potential significance for therapeutic strategies for rescue of cone-rich retinal regions affected by disease in the aging human population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 40 publications
5
44
1
Order By: Relevance
“…The role(s) played by RPE65 in providing chromophore for cone function and/or survival remains unclear and controversial (1,3,40,(43)(44)(45)(46)(47)(48)(49). Restoration of cone-as well as rod photoreceptor-based visual function by subretinal AAV gene therapy in the canine model of RPE65-LCA (4,8), together with the existence of remnant cone function in patients with untreated RPE65-LCA (3), suggested a potential to improve cone function in patients undergoing gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The role(s) played by RPE65 in providing chromophore for cone function and/or survival remains unclear and controversial (1,3,40,(43)(44)(45)(46)(47)(48)(49). Restoration of cone-as well as rod photoreceptor-based visual function by subretinal AAV gene therapy in the canine model of RPE65-LCA (4,8), together with the existence of remnant cone function in patients with untreated RPE65-LCA (3), suggested a potential to improve cone function in patients undergoing gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the majority of researchers have found that in the RPE65 knock-out mouse, both rod and cone photoreceptors were severely impaired (Fan et al, 2003;Feathers et al, 2008;Seeliger et al, 2001;Wenzel et al, 2007), Redmond et al had shown that although rod-driven ERG responses were abolished, cone function still remained intact. This finding led them to speculate that cones might use a different pathway for regenerating their pigment.…”
Section: Vision In Canonical Cycle-deficient Zebrafishmentioning
confidence: 99%
“…Thus, cone photoreceptors were thought to rely entirely on the canonical visual cycle for chromophore regeneration (Fan et al, 2003;Feathers et al, 2008;Seeliger et al, 2001;Wenzel et al, 2007). This hypothesis has been challenged by the recent findings of Wang and Kefalov, who provided clear evidence for an intra-retinal visual cycle in the rod-dominant mouse and salamander, which will be discussed in more detail below .…”
Section: Alternative Cone Visual Cycle In Cone-dominant Speciesmentioning
confidence: 99%
See 2 more Smart Citations